European Agreement Concerning the International Carriage of Dangerous Goods by Road (ADR): Applicable as from 1 January 2019 - United Nations Economic Commission for Europe (United Nations, 2018)
The European Agreement concerning the International Carriage of Dangerous Goods by Road (ADR) is intended to increase the safety of international transport of dangerous goods by road. Regularly amended and updated since its entry into force, it contains the conditions under which dangerous goods may be carried internationally. This version has been prepared on the basis of amendments applicable as from 1 January 2019.